2021
DOI: 10.12688/f1000research.26834.2
|View full text |Cite
|
Sign up to set email alerts
|

Use of chicken feather meal fermented with Bacillus subtilis in diets to increase the digestive enzymes activity and nutrient digestibility of silver pompano Trachinotus blochii (Lacepede, 1801)

Abstract: Background: Feather has the potential to be used as a fish feed ingredient because it has high protein content (80-85%), and is rich in amino acids arginine, leucine, isoleucine and valine. However, the protein consists mainly of keratin, which is classified as fiber that is difficult to digest. Therefore, to improve digestibility, the keratin protein is degraded using microbial Bacillus subtilis. This study aimed to determine the digestibility of fermented feather meal (FFM) in silver pompano (Trachinotus blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Because the growth of bacteria is strongly supported by environmental factors and nutrients they have. [14]…”
Section: Resultsmentioning
confidence: 99%
“…Because the growth of bacteria is strongly supported by environmental factors and nutrients they have. [14]…”
Section: Resultsmentioning
confidence: 99%
“…However, Ha et al (2021) explained that FM up to 50% could be successfully replaced with the same CBM used in this study in olive flounder feed without supplementation of essential AA including arginine, lysine, and methionine that are likely to be lack or deficient in CBM in diets substituting FM with CBM fulfilled their dietary requirements for olive flounder. Furthermore, the digestibility of protein in CBM including viscera, feather, and plasma is relatively low over FM (Adelina et al, 2021; Giri et al, 2000; Li et al, 2019), which could also account for the inferior growth performance of abalone fed CBM100 diet compared to abalone fed CBM0 diet. Unlike these studies, however, Tabinda and Butt (2012) found that FM could be totally (100%) replaced with chicken intestine by‐product in a 30% FM‐based diet without compromising the growth performance of grass carp ( Ctenopharyngodon idella ) fry.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, SSF of a specific feed ingredient has become a new means to develop new feed sources and reduce the usage of fishmeal in feed. Relative research focuses on fermented soybean meal [14], cottonseed meal [15], and feather meal [16]. During the fermentation process, microorganisms can break down complex nutrients such as starch and fiber, which are difficult for aquatic animals to digest and absorb, into easily digestible molecules [17,18].…”
Section: Introductionmentioning
confidence: 99%